Optimalisasi Gerakan Nusantara Tekan Obesitas (GENTAS) pada Remaja - Helfi Rahmawati; Tina Yuli Fatmawati; Nel Efni; Ariyanto Ariyanto (Jurnal Abdimas Kesehatan (JAK), 2023)
The nutritional problems in adolescents is obesity. Obesity is excessive accumulation of fat due to an imbalance between energy intake and energy expenditure for a long time. Riskesdas data on individual food consumption survey analysis of 40.7% of Indonesians consume fatty foods, 53.1% consume sweet foods, 93.5% consume less vegetables and fruit, and 26.1% lack physical activity . The purpose of this service is to increase students' knowledge about the Archipelago Movement to Reduce Obesity Rates (GENTAS), efforts to prevent and control obesity. The activities are carried out from November to January 2023 at SMPN 8 Jambi City. The target of dedication is 25 students of SMP N 8. Methods include lectures, discussions, simulations and anthropometric examinations. Results obtained there was an increase in students' knowledge after being given health education about the Archipelago Movement to Reduce Obesity at SMP N Jambi city by 88% and those who had sufficient knowledge by 22%. It was suggested to parents especially mothers to be more selective in presenting the daily food menu, teaching children healthy life behavior such as consumption of fruits and vegetables and doing physical activity/exercise every day